Pengaruh Green Accounting dan Sales Growth Terhadap Tax Avoidance pada Perusahaan Sektor Basic Material dengan Sertifikasi ISO 14001 - Simbolon, Betaria; Waty, Lenita; Hutabarat, Francis M (Jurnal Ekonomis, 2025)
Tax is an obligation that must be fulfilled by tax subjects to the government. Companies are one of the main tax subjects which have an important role in state income. For companies, taxes can be a burden that has the impact of reducing company profits, while for countries taxes function as a source of funding for various government expenditures. Given these defferences in interests, companies often manage the tax burden they face, either through legal or illegal  means. One legitimate strategy that is commonly implemented is tax avoidance. This study aims to test and analyze the effect of green accounting, sales growth on tax avoidance in basic materials sector companies listed on the indonesia stock exchange for the 2018-2023 period. This research data uses purposive sampling methood bye observing 102 data from 17 companies. The research analysis technique uses descriptive statistical analysis, t test, f test, multiple linear regression, and coefficient of determination. The test results in the study show that green accounting and sales growth simultaneously have no influence on tax avoidance. Partially, green accounting has no influence on tax avoidance, so partial sales growth has a significant influence on tax avoidance.